Peningkatan Hasil Belajar Siswa Melalui Penerapan Strategi Pembelajaran Index Card Match pada Mata Pelajaran IPA Kelas V di SDN Tondo - aqidatul izzah123; Surahman; fahriadi; Rizal (JURNAL DIKDAS, 2024)
The formulation of the problem in this research is how the application of the Index Card Match learning strategy can influence student learning outcomes in science subjects in class V elementary school? This research aims to improve student learning outcomes through implementing the Index Card Match learning strategy in science subjects in class V elementary school. In this study, the researcher used a research sample of 29 students in class VB at SDN Tondo. The type of research used is classroom action research which is carried out in cycles. The instruments used by researchers in collecting data were observation sheets, test questions, interviews and documentation. The data analysis techniques used in this research are qualitative and quantitative analysis. The results of the research show that the application of the Index Card Match strategy in class V science subjects at SDN Tondo can improve student learning outcomes. This can be seen from the results of students' classical learning completion in cycle I which was 48.3%. Then in cycle II the students' classical learning completeness score was 86.2%. There was an increase in scores from cycle I to II of 37.9%.